ANALISIS DAMPAK FLUKTUASI HARGA KARET TERHADAP KESEJAHTERAAN MASYARAKAT DUSUN KUALA SAMBEH KABUPATEN LANDAK - Ayub, Ayub; Asriati, Nuraini; Okianna, Okianna (Universitas Tanjungpura, 2025)
Indonesia is the second largest rubber producer in the world and plays an important role in the supply of rubber to the global market. Rubber prices fluctuated from January 2022 to June 2024. This study aims to determine the trend of rubber price fluctuations from 2022 to 2024 and to determine the impact of rubber price fluctuations on the welfare of the Kuala Sambeh Hamlet community, Rantau Panjang Village, Landak Regency. This study applies a qualitative approach through a case study method. Data were collected using interview techniques, including in-depth interviews using three methods, namely observation, interviews, and documentation. The informants in this study were 8 rubber farmers. The results of the study (1) show that the trend of rubber price fluctuations from 2022 to 2024 experienced price fluctuations that were balanced between rising and falling prices, but the price decline was greater or sharper than the price increase. (2) Fluctuations in rubber prices have a very negative impact on the welfare of the Kuala Sambeh Hamlet community, the community is unable to meet the welfare indicators, namely balancing income and daily expenses and education levels.